2020
DOI: 10.1126/science.aaz3480
|View full text |Cite
|
Sign up to set email alerts
|

Observation and control of maximal Chern numbers in a chiral topological semimetal

Abstract: Topological semimetals feature protected nodal band degeneracies characterized by a topological invariant known as the Chern number (C). Nodal band crossings with linear dispersion are expected to have at most |C|=4, which sets an upper limit to the magnitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
100
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 50 publications
4
100
0
1
Order By: Relevance
“…However, qualitatively, our ARPES data are consistent with some of the earlier ARPES reports [54,55]. Next, coming to the main point of this paper, recent ARPES and theoretical reports on CoSi and RhSi showed topological surface Fermi arcs spanned over a large area of two-dimensional (2D) Brillouin zone [36,37,39,[40][41][42][43][44]90]. Moreover, they could record manyfold bulk Weyl fermions at and R high symmetry points.…”
Section: Resultssupporting
confidence: 91%
“…However, qualitatively, our ARPES data are consistent with some of the earlier ARPES reports [54,55]. Next, coming to the main point of this paper, recent ARPES and theoretical reports on CoSi and RhSi showed topological surface Fermi arcs spanned over a large area of two-dimensional (2D) Brillouin zone [36,37,39,[40][41][42][43][44]90]. Moreover, they could record manyfold bulk Weyl fermions at and R high symmetry points.…”
Section: Resultssupporting
confidence: 91%
“…These crossings act as a source (red dot) or a sink (blue dot) of Berry curvature. They correspond to a Chern number of magnitude 4, i.e., the maximum Chern number achievable at a multifold node crossing 22 , and reverse sign under a mirror operation 23 . Note that, contrary to non-chiral topological semimetals, these crossings are well-separated in energy.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly important in the present case. Photoemission studies have shown that Fermi arcs are overlapping with topologically trivial bulk bands for occupied states, complicating their identification 23 . On the other hand, theoretical calculations predict them to become strongly decoupled from bulk states at positive energies, a scenario favoring their experimental detection (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the wide separation between opposite topological charges in the momentum space, the absence of mirror symmetry also leads to their large separation in energy space, providing an ideal platform for the study of quantized circular photogalvanic effects (CPGE) [3,5,7,8]. Following their theoretical predictions, long Fermi arcs, high-order degenerated band crossings, and topological CPGE were soon observed in the expected chiral crystals via angle-resolved photoemission spectroscopty (ARPES) [9][10][11][12][13], scanning tunneling microscopy (STM) [14], and optical measurements [15][16][17].…”
mentioning
confidence: 99%
“…Recently, based on ARPES and STM measurements, a sign change was detected in the Fermi velocity of surface Fermi arcs in semimetals possessing chiral multifold fermions and crystals of opposite chiralities. This implied a deep relationship between chiral lattices in the real space and chiral fermions in the momentum space [13,14,18]. This relationship offers a degree of freedom to modulate chiral fermions and their corresponding physical properties.…”
mentioning
confidence: 99%